Efficacy and safety of namilumab, a human monoclonal antibody against granulocyte-macrophage colony-stimulating factor (GM-CSF) ligand in patients with rheumatoid arthritis (RA) with either an inadequate response to background methotrexate therapy or an inadequate response or intolerance to an anti-TNF (tumour necrosis factor) biologic therapy: a randomized, controlled trial - Taylor, Peter C; Saurigny, Didier; Vencovsky, Jiri; Takeuchi, Tsutomu; Nakamura, Tadashi; Matsievskaia, Galina; Hunt, Barbara; Wagner, Thomas; Souberbielle, Bernard; NEXUS Study Group (Arthritis research & therapy, 2019)
BACKGROUND: Namilumab (AMG203), an immunoglobulin G1 monoclonal antibody that binds with high affinity to granulocyte-macrophage colony-stimulating factor (GM-CSF), was evaluated in a phase II randomized, double-blind, placebo-controlled study to investigate the efficacy and safety in patients with rheumatoid arthritis (RA) with an inadequate response to methotrexate (MTX-IR) or anti-tumour necrosis factor therapy (TNF-IR). METHODS: Subcutaneous namilumab (20, 80, or 150 mg) or placebo was administered at baseline and weeks 2, 6, and 10 in patients on stable background methotrexate therapy who were with MTX-IR or TNF-IR. Primary endpoint was mean change from baseline in the 28-joint Disease Activity Score, C-reactive protein version (DAS28-CRP) at week 12 comparing each of the three doses of namilumab to placebo. Safety and tolerability were assessed by adverse events (AEs) and pulmonary parameters. Results were analysed using the per-protocol population. RESULTS: One hundred eight patients from Europe and Japan (48.4 ± 12.02 years old; 77.8% female; mean DAS28-CRP 5.60-5.79; rheumatoid factor/anti-citrullinated protein antibodies + 75%) were randomized to placebo or namilumab 20, 80, or 150 mg (n = 27, 28, 25, and 28, respectively). Ninety-two were MTX-IR; 16 were TNF-IR. At week 12, a statistically significant difference in DAS28-CRP (p = 0.005) was seen for namilumab 150 mg versus placebo and separation was seen as early as week 2 for namilumab 150 mg (p < 0.05), with higher ACR50 and response rates versus placebo at week 12. A dose-response effect was observed across the DAS28-CRP endpoint with separation versus placebo evident from week 2. The most common treatment-emergent AEs were nasopharyngitis (18.5%, 17.9%, 4.0%, 14.3%), dyspnoea (0.0%, 3.6%, 8.0%, 10.7%), bronchitis (7.4%, 3.6%, 4.0%, 3.6%), and headache (3.7%, 3.6%, 12.0%, 0.0%) for placebo and 20, 80, or 150 mg of namilumab, respectively. No serious infections were observed. One serious AE (myocardial infarction) was observed with 150 mg of namilumab. There was no apparent dose relationship for AEs. A biomarker-based disease activity score showed a dose-dependent decrease at week 12. CONCLUSIONS: This phase II study demonstrates the benefit of inhibiting macrophage activity targeting the GM-CSF for RA. The study met its primary endpoint with a clear dose-response effect. An acceptable tolerability profile was demonstrated over the 12-week study. TRIAL REGISTRATION: ClinicalTrials.gov, NEXUS; NCT02379091 , submitted November 28, 2014.
Keywords: dospělí; vztah mezi dávkou a účinkem léčiva; Arthritis, Rheumatoid; Female; Rheumatoid arthritis; revmatoidní artritida; Namilumab; Adult; výsledek terapie; ženské pohlaví; Tumor Necrosis Factor-alpha; lidé; dvojitá slepá metoda; injekce subkutánní; Treatment Outcome; Methotrexate; TNF-alfa; Dose-Response Relationship, Drug; Double-Blind Method; Granulocyte-Macrophage Colony-Stimulating Factor; Male; Aged; methotrexát; Antirheumatic Agents; Injections, Subcutaneous; GM-CSF; lidé středního věku; humanizované monoklonální protilátky; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; antirevmatika; Middle Aged; faktor stimulující granulocyto-makrofágové kolonie; Humans